1999
DOI: 10.1002/(sici)1097-4628(19990321)71:12<2069::aid-app17>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and adsorption properties for metal ions of crosslinked chitosan acetate crown ethers

Abstract: ABSTRACT:Two novel chitosan derivatives-crosslinked chitosan dibenzo-16-c-5 acetate crown ether (CCTS-1) and crosslinked chitosan 3,5-di-tert-butyl dibenzo-14-c-4 diacetate crown ether (CCTS-2)-were synthesized by the reaction of crosslinked chitosan with dibenzo-16-c-5 chloracetate crown ether and 3,5-di-tert-butyl dibenzo-14-c-4 dichloracetate crown ether with the intent of forming polymers that could be used in hazardous waste remediation as toxic metal-binding agents in aqueous environments. Their structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(17 citation statements)
references
References 6 publications
1
16
0
Order By: Relevance
“…These are water insoluble but they swell considerably with the addition of water or aqueous metal salt solutions. Much recent research deals with this topic and its metal chelating capacity [6][7][8][9][10][11][12][13] . This type of material, with a large capacity for water retention, is known as a hydrogel.…”
Section: Introductionmentioning
confidence: 99%
“…These are water insoluble but they swell considerably with the addition of water or aqueous metal salt solutions. Much recent research deals with this topic and its metal chelating capacity [6][7][8][9][10][11][12][13] . This type of material, with a large capacity for water retention, is known as a hydrogel.…”
Section: Introductionmentioning
confidence: 99%
“…The values of the monolayer adsorption capacity of the adsorbent q max and the Langmuir constant b were calculated for nickel adsorption by plotting the graph between Ce and Qe and are reported in table 1. The q max value for nickel (II) ions was 10.82 mg/g which is higher from the other adsorbents previously studied for nickel adsorption from aqueous medium [27][28][29][30][31][32] ; for detailed comparison of q max , please see Table 2. According to Freundlich model, value of constants, K and n, are found to be 0.446 and …”
Section: Adsorption Isothermsmentioning
confidence: 78%
“…The selective chelating properties exhibited by crown ethers towards metal ions have led to their incorporation into chitosan polymer matrices to improve capacity for metal ion adsorption [1][2][3], enhance selective pollutant removal [4,5], and thus wastewater remediation [6,7]. While many authors have chemically modified crosslinked chitosan with crown ethers [5,6,[8][9][10][11][12][13][14][15][16][17], and shown the advantage of combining crown ethers with chitosan [5,8,9,18,19], only a few have used the crown ether as the crosslinker for chitosan [7,18,[20][21][22][23][24] and fewer have used the nitrogen containing azacrown ethers [25]. Using the azacrown ether as the crosslinker has the advantage that the consumption of the -NH 2 chelating group of the chitosan might be compensated by the azacrown ether chelating property.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, nitrogen containing azacrown ethers are particularly interesting due to their stronger complexation properties for heavy-metal ions [1,[26][27][28] than the all-oxygen crowns, which strongly complex alkali and alkaline earth metal [26,28]. For example, Ding et al [25] used N,N -diallyl dibenzo-18-crown-6 crown to crosslink chitosan and revealed that these materials performed better in metal ion adsorption than neat Ch owing to the presence of the crown ethers [15,16,22,23]. Structural elucidation of the products suggested that these crown ethers crosslink chitosan, although no report of gel content or network formation was presented in this work and others [10,11,15,16,20,23].…”
Section: Introductionmentioning
confidence: 99%